2016
DOI: 10.12688/f1000research.9765.1
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome of Pieris rapae, a resilient alien, a cabbage pest, and a source of anti-cancer proteins

Abstract: The Small Cabbage White ( Pieris rapae) is originally a Eurasian butterfly. Being accidentally introduced into North America, Australia, and New Zealand a century or more ago, it spread throughout the continents and rapidly established as one of the most abundant butterfly species. Although it is a serious pest of cabbage and other mustard family plants with its caterpillars reducing crops to stems, it is also a source of pierisin, a protein unique to the Whites that shows cytotoxicity to cancer cells. To bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 64 publications
2
42
0
Order By: Relevance
“…). This is within range of what could be expected based on the number of genes identified in other Lepidoptera taxa (Challis, Kumar, Dasmahapatra, Jiggins, & Blaxter, ; Cong et al., ; Nowell et al., ; Shen et al., ; The Heliconius Genome Consortium ). This analysis also showed that transcriptomes based on individual treatments or development stages had a smaller number of transcripts than when libraries were combined – the optimized transcriptome for example consisted of 21,189 transcripts (Fig.…”
Section: Methodssupporting
confidence: 77%
“…). This is within range of what could be expected based on the number of genes identified in other Lepidoptera taxa (Challis, Kumar, Dasmahapatra, Jiggins, & Blaxter, ; Cong et al., ; Nowell et al., ; Shen et al., ; The Heliconius Genome Consortium ). This analysis also showed that transcriptomes based on individual treatments or development stages had a smaller number of transcripts than when libraries were combined – the optimized transcriptome for example consisted of 21,189 transcripts (Fig.…”
Section: Methodssupporting
confidence: 77%
“…We sequenced and annotated 23 reference genomes of butterflies from the United States. Combined with the 13 genomes published previously (3)(4)(5)(6)(7)(8)(9)(10)(11)(20)(21)(22)(23)) (8 by our group), a total of 36 reference genomes are used in this study. The N50 of the new genomic assemblies ranges from 50 to 3,700 kb, and they are over 95% complete in essential genes (24) ( Table 1).…”
Section: Reference Genomes Of Butterfliesmentioning
confidence: 99%
“…We sequenced, assembled and annotated genomes as previously described (6,9,11). Briefly, paired-end libraries with insert sizes 250 bp and 500 bp and mate-pair libraries with insert sizes 2 kb, 5 kb, and 10 kb were constructed and sequenced.…”
Section: Reference Genome Assembly and Annotationmentioning
confidence: 99%
See 2 more Smart Citations